Mindfulness and rehabilitation: teaching yoga and meditation to young men in an alternative to incarceration program - Barrett, Carla J. (International journal of offender therapy and comparative criminology, 2017)
This study used participant/observation and open-ended interviews to understand how male participants (age 18-24 years) benefited from yoga and mindfulness training within an Alternative to Incarceration (ATI) program. Findings suggest that the male participants (age 18-24 years) benefited from the intervention through reductions in stress and improvements in emotion regulation. Several participants noted the importance of the development of an embodied practice for assisting them in managing anger and impulse control. The young men’s narratives suggest that mindfulness-based interventions can contribute positively to rehabilitative outcomes within alternative to incarcerations settings, providing complementary benefit to existing ATI programs, especially for clients amenable to mindfulness training. With many jurisdictions expanding rehabilitation-focused interventions for young offenders, service providers should consider the potential positive contributions that mindfulness-based interventions can have for fostering desistance and reducing recidivism among justice system–involved populations.